Intensive vital signs monitoring reduces 30-day mortality among stroke patients: A cohort study from Tanzania - Basil Tumaini; Ipyana Kunjumu; Mohamed Mnacho; Patricia Munseri (PLoS ONE, 2025)
Background Stroke is a leading cause of mortality and disability worldwide, with disproportionate impacts in low- and middle-income countries due to limited healthcare resources. Monitoring vital signs during the acute phase of a stroke is critical for detecting complications. We aimed to assess the impact of intensive (6-hourly) versus usual practice (12-hourly) vital sign monitoring strategies on stroke outcomes at Mloganzila Hospital, Tanzania. Methods We conducted a prospective cohort study of patients with first-ever stroke admitted to Mloganzila Hospital between October 2023 and March 2024. Participants were assigned to 6-hourly or 12-hourly vital signs monitoring for the first 72 hours, after which all received usual care. Monitoring frequency reflected routine clinical practice; no investigational treatments were introduced, and therapeutic decisions were unaffected by group allocation. The primary outcome was 30-day all-cause mortality; secondary outcomes included functional disability measured by the modified Rankin Scale. Ethical approval was obtained, and informed consent was secured. Data were analyzed using SPSS version 26 and Stata version 15. Survival was assessed using Kaplan-Meier analysis, and factors associated with 30-day mortality identified using modified Poisson regression. Results Of 306 participants (mean age: 59.6 ± 14.0 years; 53.6% male), 63.7% experienced a hemorrhagic stroke. There were no significant differences in stroke severity or functional disability at 72 hours between the groups. Intensive vital signs monitoring was associated with significantly lower 30-day mortality compared to usual monitoring (35.9% vs. 49.7%; p = 0.015). Conclusion Frequent monitoring of vital signs during the acute phase of stroke may enhance clinical stability and improve patient outcomes. Our findings demonstrate a significant reduction in 30-day mortality with intensive monitoring. These findings support the establishment of dedicated stroke units with structured monitoring protocols in resource-limited settings to strengthen stroke care systems and reduce preventable deaths.